Simplify: `3sqrt(4)sqrt(5)sqrt(7)`3 square root 4 square root 5 square root 7 Topic: Math 1 Answer | Add Yours durbanville | High School Teacher | (Level 2) Educator Emeritus Posted on November 13, 2012 at 4:18 AM `3sqrt(4)sqrt(5)sqrt(7)` = `3 (2) sqrt(35)` or `3(-2)sqrt(35)` = `6sqrt(35)` or `-6sqrt(35)` `3sqrt(4)sqrt(5)sqrt(7)` = `3 (2) sqrt(35)` or `3(-2)sqrt(35)` = `6sqrt(35)` or `-6sqrt(35)` We’ve answered 301,389 questions. We can answer yours, too. Ask a question

durbanville | High School Teacher | (Level 2) Educator Emeritus Posted on November 13, 2012 at 4:18 AM `3sqrt(4)sqrt(5)sqrt(7)` = `3 (2) sqrt(35)` or `3(-2)sqrt(35)` = `6sqrt(35)` or `-6sqrt(35)` `3sqrt(4)sqrt(5)sqrt(7)` = `3 (2) sqrt(35)` or `3(-2)sqrt(35)` = `6sqrt(35)` or `-6sqrt(35)`